Performance assessment of Heat Recovery Steam Generator at district Cooling plant - Nordin, A. (Asian Research Publishing Network, 2015)
Heat Recovery Steam Generators are important components in cogeneration plants. The steam produced by the Heat Recovery Steam Generator is used to produce chilled water at a District Cooling plant. The performance of the Heat Recovery Steam Generator will affect the performance of the overall District Cooling plant. This study presents the performance of the Heat Recovery Steam Generator which is based on the first and second laws of the thermodynamic principle. The following parameters, energy efficiency, exergy efficiency, exergy of fuel, exergy of product and exergy destruction of the Heat Recovery Steam Generator were analysed. The results showed that as the mass flow rate of fuel increased, the energy and exergy efficiencies of the Heat Recovery Steam Generator increased. From the results of the exergy analysis, the exergy destruction indicated the presence of the inefficiencies of the Heat Recovery Steam Generator. In order to obtain a higher performance of the Heat Recovery Steam Generator, the value of the exergy destruction must be lower. Â© 2006-2015 Asian Research Publishing Network (ARPN).